2022
DOI: 10.1093/ajcn/nqac083
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation in chronic obstructive pulmonary disease patients with low serum vitamin D: a randomized controlled trial

Abstract: Background Vitamin D deficiency is frequently found in patients with Chronic Obstructive Pulmonary Disease (COPD). Vitamin D has antimicrobial, anti-inflammatory and immunomodulatory effects. Therefore, supplementation may prevent COPD exacerbations, particularly in deficient patients. Objectives To assess the effect of vitamin D supplementation on exacerbation rate in vitamin D-deficient patients with COPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
2
24
0
1
Order By: Relevance
“…Lokesh et al [17] found a positive correlation between serum 25(OH)D 3 levels and 6-min walk test (6MWT) distance in patients with COPD but not in healthy controls, suggesting that there may be an additional role of vitamin D in the musculoskeletal system for patients with COPD. However, Rafiq et al [21 ▪▪ ] found that vitamin D supplementation did not improve 6MWT distance in COPD patients.…”
Section: The Effects Of Vitamin D Deficiency and Treatment In Chronic...mentioning
confidence: 96%
See 2 more Smart Citations
“…Lokesh et al [17] found a positive correlation between serum 25(OH)D 3 levels and 6-min walk test (6MWT) distance in patients with COPD but not in healthy controls, suggesting that there may be an additional role of vitamin D in the musculoskeletal system for patients with COPD. However, Rafiq et al [21 ▪▪ ] found that vitamin D supplementation did not improve 6MWT distance in COPD patients.…”
Section: The Effects Of Vitamin D Deficiency and Treatment In Chronic...mentioning
confidence: 96%
“…The reported relationship between VDD and COPD exacerbations has prompted some investigators to study the impacts of vitamin D replacement on exacerbations (Table 1). In one recent randomized control trial (RCT), 155 COPD patients were randomized to receive 16 800 units of vitamin D 3 oral weekly or placebo but there was no difference in the rate of exacerbations between the treatment arms despite improvement in serum 25(OH)D 3 levels [serum 25(OH)D 3 levels 38 ± 15 to 112 ± 34 nmol/l in the treatment group compared with 40 ± 17 to 42 ± 17 nmol/l in placebo] [21 ▪▪ ]. Another recent RCT found no benefit of vitamin D replacement on the rate of exacerbations in the treatment group overall, but there was a significant benefit in the subgroup of patients with serum 25(OH)D 3 levels less than 25 ng/ml when given vitamin D 3 100 000 units oral monthly compared with placebo (hazard ratio 0.11, 95% CI 0.01–0.51) [28 ▪▪ ].…”
Section: The Effects Of Vitamin D Deficiency and Treatment In Chronic...mentioning
confidence: 99%
See 1 more Smart Citation
“…, the effects of vitamin D supplementation in COPD patients with vitamin D deficiency was investigated. Their findings failed to show any preventive or positive effects of vitamin D supplementation on lung exacerbations [ 46 ]. They mentioned several factors contributing to their results.…”
Section: Vitamin D and Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…Collectively, they concluded no effect of vitamin D supplementation on reducing exacerbations in COPD patients with vitamin D supplementation. Nonetheless, they highlighted the need of supplementing COPD patients with a serum 25(OH)D concentration < 124.8 ng/ml, as COPD patients having low vitamin D are diagnosed with osteoporosis and bone fractures [ 46 , 47 , 51 , 52 ]. By contrast, other RCT studies that aimed similar clinical outcomes [ 53 , 54 ], showed that vitamin D supplementation was associated with a decrease in COPD exacerbations, increase in FEV 1 [ 53 ] and increase in serum 25(OH)D levels [ 54 ].…”
Section: Vitamin D and Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%